Special strength training manual for coaches - Verkhoshansky, Y.; Verkhoshansky, N. (Verkhoshansky SSTM, 2011)
The Coaches Manual is the most cutting edge and exhaustive work of its kind. The reader can find in it all the fundamental theoretic elements of the SST as well as practical indications for the means and methods and many programs for cyclic, acyclic, sport games and combat sports.In it contains elucidation of rationale of organizing Special Strength Training and its application within the Block Training System which has been widely explained for the first time in a book. All its content comes from experiments and application in field of the authors.